[18F]ODIBO: a prosthetic group for bioorthogonal radiolabeling of macromolecules via strain-promoted alkyne–azide cycloaddition. Issue 3 (24th November 2017) - Boudjemeline, Mehdi; McNitt, Christopher D.; Singleton, Thomas A.; Popik, Vladimir V.; Kostikov, Alexey P.
Abstract : [ 18 F]oxadibenzocyclooctyne ([ 18 F]ODIBO) allows for efficient biorthogonal radiolabeling of macromolecules at low concentrations and room temperature via SPAAC. Abstract : A novel prosthetic group for the efficient radiolabeling of macromolecules has been developed. [ 18 F]oxadibenzocyclooctyne ([ 18 F]ODIBO) is synthesized in high radiochemical yield and applied for nearly quantitative conjugation to azide-tagged peptides and proteins at room temperature and low substrate concentrations. The resulting bioconjugates are chemically and radiochemically pure and free of toxic solvents and catalysts.